Luminol-based bioluminescence imaging of mouse mammary tumors - Alshetaiwi, Hamad S.; Balivada, Sivasai; Shrestha, Tej Bahadur; Pyle, Marla M.; Basel, Matthew T.; Bossmann, Stefan H.; Troyer, Deryl L. (My University, 2013)
Polymorphonuclear neutrophils (PMNs) are the most abundant circulating blood leukocytes. They are part of the innate immune system and provide a first line of defense by migrating toward areas of inflammation in response to chemical signals released from the site. Some solid tumors, such as breast cancer, also cause recruitment and activation of PMNs and release of myeloperoxidase. In this study, we demonstrate that administration of luminol to mice that have been transplanted with 4T1 mammary tumor cells permits the detection of myeloperoxidase activity, and consequently, the location of the tumor. Luminol allowed detection of activated PMNs only two days after cancer cell transplantation, even though tumors were not yet palpable. In conclusion, luminol-bioluminescence imaging (BLI) can provide a pathway towards detection of solid tumors at an early stage in preclinical tumor models.
Keywords: Bioluminescence; Chemiluminescence; Neutrophil; Luminol; Cancer detection; Murine breast cancer model